A randomized, double-blinded, phase 2 trial of EDP1815, an oral immunomodulatory preparation of Prevotella histicola, in adults with mild-to-moderate plaque psoriasis - Ehst, Benjamin D.; Strober, Bruce; Blauvelt, Andrew; Maslin, Douglas; Macaro, Debbie; Carpenter, Nancy; Bodmer, Mark; McHale, Duncan (Frontiers in Medicine, 2024)
Background: Psoriasis is a chronic inflammatory skin disease. EDP1815 is an oral, gut-restricted preparation of non-live Prevotella histicola, the first of a new immunomodulatory therapeutic class targeting the small intestine to generate systemic anti-inflammatory responses. Objective: To evaluate safety and efficacy of EDP1815 in mild-to-moderate psoriasis in a proof-of-concept study. Methods: A phase 2, multicenter, randomized, double-blinded, placebo-controlled, parallel-group study with a 16-week treatment period and up to 24 weeks of follow-up. Participants were randomized to receive 1, 4, or 10 capsules daily. Results: EDP1815 was well tolerated with comparable rates of treatment-emergent adverse events to placebo, and no drug-related serious adverse events. Clinically meaningful responses to EDP1815, defined as at least 50% reduction in Psoriasis Area and Severity Index (PASI-50) at week 16, were observed in all 3 cohorts, statistically significant in the 1-capsule (29.7%; P = .048) and 4-capsule (31.9%; P = .022) groups, compared with placebo (12.1%). Among EDP1815-treated PASI-50 responders at week 16, 60% (18/30) maintained or improved off-treatment responses at week 40. Limitations: Continued off-treatment improvement past 16 weeks shows potential for greater therapeutic benefit that was not assessed. Conclusion: EDP1815 was well-tolerated with a placebo-like safety profile, and had meaningful efficacy outcomes in psoriasis, validating this novel immunomodulatory approach.